The Promise of the Trans* Body: Twisted Liminalities of Gender in Transparent. (October 2020) - Carlson, David Lee; Sweet, Joseph David
This article employs the feminist thought of Helene Cixous to explore the liminality of gender. It does so through the story of Maura in the popular television show, Transparent . The article begins with a review of the history of the term "transgender" and links it to Cixous's theory. After explicating Cixous's theory, we "wander" through the character of Maura. We use Cixous's notion of wandering to show how Maura moved from being the patriarch of the family to being a trans* woman. The article illustrates how liminality of gender exists as a whirlpool and as a promise for gender to be written as text as flesh.